2010
DOI: 10.1016/j.vetmic.2009.10.023
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference inhibits hepatitis E virus mRNA accumulation and protein synthesis in vitro

Abstract: Hepatitis E virus (HEV) is a zoonotic pathogen to which several species, including human beings, pigs and rodents, are reported to be susceptible. To date, vaccines developed against HEV still need to be improved and a structural gene (ORF2), which encodes a capsid protein with high sequence conservation found across HEV genotypes, is a potential candidate. To exploit the possibility of using RNA interference (RNAi) as a strategy against HEV infection, four small interference RNA (siRNA) duplex targeting ORF2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Mono- and di-hammerhead ribozymes designed against the 3′ end of the HEV genomic RNA were shown to inhibit expression from a reporter construct in HepG2 cells ( Sriram et al, 2003 ). In A549 cells infected with HEV, small interfering RNAs (siRNAs) against the orf2 region were shown to offer protection ( Huang et al, 2010 ). While such approaches are feasible in vitro , the delivery and targeting of such inhibitors in vivo would be the real challenge.…”
Section: Potential Targets and Antiviral Agentsmentioning
confidence: 99%
“…Mono- and di-hammerhead ribozymes designed against the 3′ end of the HEV genomic RNA were shown to inhibit expression from a reporter construct in HepG2 cells ( Sriram et al, 2003 ). In A549 cells infected with HEV, small interfering RNAs (siRNAs) against the orf2 region were shown to offer protection ( Huang et al, 2010 ). While such approaches are feasible in vitro , the delivery and targeting of such inhibitors in vivo would be the real challenge.…”
Section: Potential Targets and Antiviral Agentsmentioning
confidence: 99%
“…For fighting viral diseases with RNAi, considerable attempts have been made to date. Previous reports demonstrated that the plasmid vector constructs containing shRNAs targeting CSFV [ 25 ], FMDV [ 26 ], TGEV [ 27 ], and PEDV [ 28 ] could effectively inhibit viral replications [ 35 , 36 , 37 , 38 ]. RNAi-based technology is becoming a potent therapeutic strategy to exert antiviral activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interference with HEV RNA replication has been attempted using ribozymes and small interfering RNAs. 123,124 Although such approaches are feasible in vitro, the delivery and targeting of such inhibitors in vivo would be the real challenge. Several recent reports show the efficacy of Ribavirin monotherapy in treating immunocompromised trans-plant patients with chronic HEV infection, [125][126][127] severe acute hepatitis E, 128 and acute on chronic liver failure.…”
Section: Antiviral Targets In Hevmentioning
confidence: 99%